Molecular Genetics Analysis of 70 Chinese Families With Muscular Dystrophy Using Multiplex Ligation-Dependent Probe Amplification and Next-Generation Sequencing - Wang, Dong; Gao, Min; Zhang, Kaihui; Jin, Ruifeng; Lv, Yuqiang; Liu, Yong; Ma, Jian; Wan, Ya; Gai, Zhongtao; Liu, Yi (Frontiers in Pharmacology, 2019)
Background Muscular dystrophy (MD) includes multiple types, of which dystrophinopathies caused by dystrophin(DMD) mutations are the most common types in children. An accurate identification of the causative mutation at the genomic level is critical for genetic counseling of the family, and analysis of genotype-phenotype correlations, as well as a reference for the development of gene therapy. Methods Totally 70 Chinese families with suspected MD probands were enrolled in the study. The multiplex ligation-dependent probe amplification (MLPA) was first performed to screen large deletions/duplications of DMD exons in the patients, and then next-generation sequencing (NGS) was carried out to detect small mutations in the MLPA-negative patients. Results Totally 62 mutations of DMD were found in 62 probands with DMD/BMD, and 2 compound heterozygous mutations in LAMA2 were identified in 2 probands with MDC1A(a type of congenital MD), indicating that the diagnostic yield was 91.4% by MLPA plus NGS for MD diagnosis in this cohort. Out of the mutations, 51 large mutations encompassing 47 (75.8%) deletions and 4 duplications (6.5%) were identified by MLPA; 11 small mutations including 6 (9.7%) nonsense, 2 (3.2%) small deletions, 2 splice-site mutations (3.2%) and 1 small insertion (1.6%) were found by NGS. Large mutations were found most frequently in the hotspot region between exons 45-55 (70.6%). Out of the 11 patients harboring point mutations in DMD, 8 were novel mutations. Additionally, one novel mutation in LAMA2 was identified. All the novel mutations were analyzed and predicted as pathogenic according to ACMG guideline. Finally 34 DMD, 4 BMD, 24 BMD/DMD and 2 MDC1A were diagnosed in the cohort. Conclusion Our data indicated that the MLPA plus NGS can be a comprehensive and effective tool for precision diagnosis and potential treatment of MD, and is particularly necessary for the patients at very young age with only two clinical indicators (persistent hyperCKemia and typical myopathy performance on electromyogram) but no definite clinical manifestations.